Мodern trends in the development of the insurance markets of the EAEU countries - Yessengeldin, B.S.; Serikova, G.S. (BUKETOV BUSINESS REVIEW, 2018)
In modern conditions, the formation of a unified insurance market in the EAEU is an integral part of the integration process as a whole. In these conditions, the role and place of the national insurance market in the integration association depends to a certain extent on its ability to function effectively so as to be competitive. Effective functioning of the insurance market is one of the important factors for the progressive development of the economy. In this regard, it is relevant to assess the development of insurance markets of the countries participating in the Eurasian Economic Union. This article provides a material on the situation in the insurance markets of the EAEU countries, and discusses the specificities of their development. Based on an analysis of the dynamics of the quantitative and qualitative indicators of the economic sector, the trends and problems of the development of the insurance markets of the EAEU countries have been identified, and the factors in the reduction of insurance premiums, payments and own capital have been identified. The authors assess the current state of the insurance markets of the EAEU, identify commonalities and differences in the development of insurance markets, show the level and potential of the insurance market in each country of the EAEU, depending on the state and pace of economic development.